Surgical Removal of Traumatic Herniation of Buccal Fat Pad in Young Children - Agrawal, NK; Dahal, S; Khadka, R (Kathmandu University Medical Journal, 2015)
Intraoral herniation of the buccal fat pad is traumatic lesion of oral cavity occurring in young children. It frequently presents as an expanding pedunculated mass of soft tissue emanating from the buccal mucosa following a minor trauma to the buccal soft tissues. This article aims to report an interesting and rare lesion, wherein a tiny traumatic perforation of the buccal mucosa and buccinator muscle forced a large portion of the buccal fat pad to extrude into the oral cavity in a young boy. Such a situation can alarm any clinician and reinforces the importance of careful history taking and thorough examination, before treating patients. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12514 Kathmandu Univ Med J 2013; 43(3):247-249